Modeling of the surface-to-surface radiation exchange using a Monte Carlo method. Issue 3 (September 2016) - Frank, A; Heidemann, W; Spindler, K
Abstract: The thermal conditions inside of switch cabinets are strongly influenced by radiation heat transfer. To achieve accurate simulation results for the temperature distribution inside of switch cabinets a surface-to-surface radiation model is developed, which calculates the net heat flows for given temperatures of the plane, grey, diffuse surfaces. The accuracy of this calculation strongly depends on exact values for the radiation view factors. A Monte Carlo method is applied to compute the view factors. Several variations for grid spacing, the number of emitted photons and a quasi-Monte Carlo method are discussed. The radiation model is validated using numerical comparative data for a switch cabinet of given size with and without electrical components inside.